Development of shape pattern recognition for fpga-based embbeded object tracking system - Fauziliana, Binti Osman (Universiti Malaysia Sarawak, (UNIMAS), 2010)
This project presents FPGA (Field Programmable Gate Array) based solution for an embedded object tracking system. The tracking design was applied at FPGA as rich information of FPGA offers one of the powerful ideas in object tracking system. Object tracking system well-known as the system that is very useful in most real application that requires object detection, for example factory camera surveillance system. There are lots of algorithms available including the detection of handwriting, moving people, animals and the barcode number. This project will focus on shape detection to observe the real object image and the expected experimental object shape image. Shapes that cover are square, circle, triangle and etc. The black and white image will be used in the design and will be converted to binary signals before entering the tracker process. Then the design system will be embedded to the FPGA to confirm the shape that obtained using Quartus II Altera software. The pixels detected represent the available of intensity within the image. No error and correction included in the system. The system represented only fixed image without noise and no assorted.